LINGUOPOETIC PARAMETERS OF PANEGYRIC “EVODIIA” BY G. BUTOVYCH - Hrytsyna, S. (Linguistic and Conceptual Worldviews, 2019)
The article is devoted to the linguopoetic analysis of the ancient text of the Baroque period, in particular the panegyric “Evodiia” by G. Butovych, which is considered both the external design of the text, and the internal linguistic elements, caused by synthesis of the Baroque author’s thinking and sociocultural guidelines of the first half of the XVII century. The sociocultural circumstances of the creation of the “Evodiia” are revealed. The external, ornamental design of the Baroque monument is described, so such aesthetic elements of the panegyric as the graphic decoration of the text by the author and the inclusion of various actual Baroque elements (acrostic, heraldic verse, visual poem etc.) and internal language units, in particular stylistic figures and tropes, creating aesthetic eﬀect are investigated. Linguopoetic parameters of “Evodiia” by G. Butovych, represented by architectonics and stylistically marked linguistic units, reveal the specifics of the panegyric as the original genre of the Baroque Period and testify to the peculiarities of the old Ukrainian literary language expressive means of the first half of the XVII century.